Aspects of the metabolism of the epidermal growth factor receptor in A431 human epidermoid carcinoma cells. - Decker, S J (1984)
The biosynthesis and posttranslational metabolism of the epidermal growth factor (EGF) receptor were examined in the A431 human epidermoid carcinoma cell line. Polyclonal antibody against the receptor specifically immunoprecipitated two [35S]methionine-labeled proteins of Mr = 160,000 and 170,000. Pulse chase experiments showed the Mr = 160,000 protein to be a precursor of the Mr = 170,000 protein. Preincubation with tunicamycin resulted in immunoprecipitation of a single band of Mr = 130,000, whereas monensin inhibited maturation to the Mr = 170,000 form. Digestion of the Mr = 160,000 and 170,000 proteins with endoglycosidase H resulted in the appearance of Mr = 130,000 and 165,000 proteins, respectively. Prolonged pulse-chase experiments indicated that the half-life of the receptor is ca. 20 h in the absence of EGF and 5 h in the presence of EGF. Approximately three- to five-fold more phosphate is incorporated into the mature receptor upon addition of EGF, due primarily to increases in levels of phosphotyrosine and phosphoserine. Phosphate was also present on the Mr = 160,000 protein and the Mr = 130,000 protein found in the presence of tunicamycin.